2019
DOI: 10.1007/s10577-019-09604-2
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the nuclear positioning of the PPARG gene for its expression during porcine in vitro adipogenesis

Abstract: Proper expression of the PPARG gene, which encodes a key transcription factor of adipogenesis, is indispensable in the formation of mature adipocytes. The positioning of a gene within the nuclear space has been implicated in gene regulation. We here report on the significance of the PPARG gene’s nuclear positioning for its activity during in vitro adipogenesis in the pig. We used an established system of differentiation of mesenchymal stem cells derived from bone marrow and adipose tissue into adipocytes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 74 publications
(83 reference statements)
1
14
0
Order By: Relevance
“…Such behavior of OCT4 alleles can be considered evidence for a correlation between gene expression and gene positioning. This is in agreement with a report by Stachecka, Nowacka-Woszuk, Kolodziejski, and Szczerbal (2019), who demonstrated that active PPARG alleles are centrally positioned when inactive. Nevertheless, our data also demonstrated that the distance of active and inactive SOX2 alleles from the nuclear membrane did not differ significantly in both 4-and 8-cell blastomeres.…”
Section: Discussionsupporting
confidence: 94%
“…Such behavior of OCT4 alleles can be considered evidence for a correlation between gene expression and gene positioning. This is in agreement with a report by Stachecka, Nowacka-Woszuk, Kolodziejski, and Szczerbal (2019), who demonstrated that active PPARG alleles are centrally positioned when inactive. Nevertheless, our data also demonstrated that the distance of active and inactive SOX2 alleles from the nuclear membrane did not differ significantly in both 4-and 8-cell blastomeres.…”
Section: Discussionsupporting
confidence: 94%
“…For example, it has been previously shown that DNA is wound into chromatin territories, with specific areas corresponding to specific genes 810 . The localization of genes within the nucleus is not random and have been demonstrated to be related to gene activation 11,12 , suggesting the reorganization of the nucleus is a prerequisite to initiate the reprogramming to a different cell lineage 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The repositioning of genes from the nuclear lamina during many differentiation processes is a well-known mechanism of transcriptional activation 58 , 59 . Our previous experiments have shown the relocation of adipogenic genes from the nuclear periphery during differentiation 6 , 8 , 23 , but further studies are needed to elucidate if the decrease in lamin plays a direct role in this reorganization.…”
Section: Discussionmentioning
confidence: 96%
“…The differentiation of progenitor cells into adipocytes is accompanied not only by characteristic changes in cell morphology (resulting in round lipid-laden cells with a rim of cytoplasm and a flattened peripherally located nucleus), but also in nuclear organization 3 , 4 . This includes changes in nucleus shape and size, reduction of lamin A/C expression, reorganization of the chromocenter, and repositioning of chromosomes and genes 4 8 . Moreover, higher-order chromatin organization and chromatin interactions have recently emerged as important regulators of gene expression during adipogenesis 9 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation